Arteriovenous access practices in Australian and New Zealand dialysis units. Issue 6 (November 2019) - Smyth, Brendan; Kotwal, Sradha; Gallagher, Martin; Gray, Nicholas A; Polkinghorne, Kevan R
Background: The creation and maintenance of dialysis vascular access is associated with significant morbidity. Structured management pathways can reduce this morbidity, yet practice patterns in Australia and New Zealand are not known. We aimed to describe the arteriovenous access practices in dialysis units in Australia and New Zealand. Methods: An online survey comprising 51 questions was completed by representatives from dialysis units from both countries. In addition to descriptive analysis, responses were compared between units inside and outside of major cities. Results: Of 64 contacted units, 48 (75%) responded (Australia 43, New Zealand 5), representing 38% of dialysis units in Australia and New Zealand. While 94% of units provided pre-dialysis education, only 60% reported a structured pre-dialysis pathway and 69% had a dedicated vascular access nurse. Most units routinely monitored fistula/graft function using flow rate measurement (73%) or recirculation studies (63%). A minority used routine ultrasound (35%). Thrombectomy, fistuloplasty and peritoneal dialysis catheter insertion were rarely performed by nephrologists (4%, 4% and 17% of units, respectively). Units outside of a major city were less likely to have access to a local vascular access surgeon (6/13 (46%) vs 35/35 (100%), P < 0.001). There were no other significant differences between units on the basis of location. Conclusion: Much variation exists in unit management of arteriovenous access. Structured pre-dialysis pathways and dedicated vascular access nurses may be underutilised in Australia and New Zealand. The use of regular access blood flow measurement and ultrasound is common in both countries despite a lack of data supporting its effectiveness. There is room for both practice improvement and a need for further evidence to ensure optimal arteriovenous access care.